Cross-sectional Neuromuscular Phenotyping Study of Patients With Arhinia With SMCHD1 Variants. (29th March 2022) - Mohassel, Payam; Chang, Ning; Inoue, Kaoru; Delaney, Angela; Hu, Ying; Donkervoort, Sandra; Saade, Dimah; Billioux, B. Jeanne; Meader, Brooke; Volochayev, Rita; Konersman, Chamindra G.; Kaindl, Angela M.; et al.
Abstract : Background and Objectives: Facioscapulohumeral muscular dystrophy type 2 (FSHD2) and arhinia are 2 distinct disorders caused by pathogenic variants in the same gene: SMCHD1 . The mechanism underlying this phenotypic divergence remains unclear. In this study, we characterize the neuromuscular phenotype of individuals with arhinia caused by SMCHD1 variants and analyze their complex genetic and epigenetic criteria to assess their risk for FSHD2. Methods: Eleven individuals with congenital nasal anomalies, including arhinia, nasal hypoplasia, or anosmia, underwent a neuromuscular examination, genetic testing, muscle ultrasound, and muscle MRI. Risk for FSHD2 was determined by combined genetic and epigenetic analysis of 4q35 haplotype, D4Z4 repeat length, and methylation profile. We also compared expression levels of pathogenic DUX4 mRNA in primary myoblasts or dermal fibroblasts (upon myogenic differentiation or epigenetic transdifferentiation, respectively) in these individuals vs those with confirmed FSHD2. Results: Among the 11 individuals with rare, pathogenic, heterozygous missense variants in exons 3–11 of SMCHD1, only a subset (n = 3/11; 1 male, 2 female; age 25–51 years) met the strict genetic and epigenetic criteria for FSHD2 (D4Z4 repeat unit length <21 in cis with a 4qA haplotype and D4Z4 methylation <30%). None of the 3 individuals had typical clinical manifestations or muscle imaging findings consistent with FSHD2. However, the patients with arhinia meeting the permissive genetic and epigenetic criteria for FSHD2 displayed some DUX4 expression in dermal fibroblasts under the epigenetic de-repression by drug treatment and in the primary myoblasts undergoing myogenic differentiation. Discussion: In this cross-sectional study, we identified patients with arhinia who meet the full genetic and epigenetic criteria for FSHD2 and display the molecular hallmark of FSHD— DUX4 de-repression and expression in vitro—but who do not manifest with the typical clinicopathologic phenotype of FSHD2. The distinct dichotomy between FSHD2 and arhinia phenotypes despite an otherwise poised DUX4 locus implies the presence of novel disease-modifying factors that seem to operate as a switch, resulting in one phenotype and not the other. Identification and further understanding of these disease-modifying factors will provide valuable insight with therapeutic implications for both diseases.